Cross-cultural adaptation to Brazilian Portuguese of the Dementia Knowledge Assessment Tool Version Two: DKAT2 - Piovezan, Marcelo [UNESP]; Miot, Helio Amante [UNESP]; Garuzi, Miriane [UNESP]; Jacinto, Alessandro Ferrari [UNESP] (Assoc Arquivos Neuro- Psiquiatria, 2018)
The Dementia Knowledge Assessment Tool Version Two (DKAT2) was developed to measure caregivers' knowledge about the trajectory of dementia and assess changes in the knowledge before and after educational programs. The DKAT2 is a 21-item tool with questions about several aspects of dementia. The possible answers for each question are yes, no or don't know. The maximum score is 21. Objective: The aim of the study was to cross-culturally adapt the DKAT2 to Brazilian Portuguese. Methods: The essential steps to cross-culturally adapt were conducted and the final version administered to 30 caregivers of older people with dementia, sampled by convenience. Results: In the sample assessed, the mean age was 55.7 (+/- 12.5) years, 93.3% were female, 56.7% were sons/daughters and 23.3% were spouses of the older adults with dementia. The mean time caring for the elder was 4.7 (+/- 3.3) years and 70% of the caregivers had some level of burden. The mean age of the older people was 82.4 (+/- 6.7) years, 19 (63.3%) had a diagnosis of Alzheimer's disease, 100% were dependent for instrumental activities of daily living and 70% had some degree of dependence for basic activities of daily living. The mean score for the caregivers' knowledge level was 15.0 (+/- 2.5) correct answers. Conclusions: The Brazilian Portuguese version was developed and the final version is suitable for use in Brazil.
Keywords: aged; caregivers; dementia; knowledge